Application of discriminant analysis to parameters describing the drape for two types of woven fabrics. Issue 6 (2nd June 2016) - Capdevila, X.; Carrera-Gallissà, E.
Abstract : A total of 33 commercial drapery and lining fabrics were used to determine the drape indicators drape ratio and R -factor. The slope of a plot of one indicator against the other was found not to afford complete characterization of drape shape for fabrics of different commercial use. In this work, further six parameters describing the drape, proposed by the authors to discriminate drape shapes were also calculated. Discriminant analysis of the data revealed that a linear combination of various parameters allowed two types of woven fabrics (viz. drapery and linen) to be distinguished. The discriminant function used accurately classified 75.76% of the fabrics studied.